2021
DOI: 10.47411/al-awqaf.v12i2.68
|View full text |Cite
|
Sign up to set email alerts
|

Survei Wakaf Hak Kekayaan Intelektual

Abstract: Meluasnya harta benda yang dapat dijadikan wakaf hadir melalui lahirnya undang-undang wakaf No. 41 tahun 2004. Salah satu hal yang menarik dalam pasal 16 Undang-Undang wakaf adalah pernyertaan ketentuan yang menyatakan bahwa Hak Kekayaan Intelektual (HKI) dapat digunakan sebagai aset/harta benda wakaf. sejalan dengan Undang-unang wakaf, pada Undang-undang yang menyangkut Hak Kekayaan Intelektual juga tercantum bahwa HKI dapat dialihkan sebagai wakaf. Namun demikian wakaf dengan harta/benda berupa Hak Kekayaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…On the other hand, the result from descriptive respondents regarding the level of understanding is not too high. These results are in accordance with Habibah et al (2019), surveying the level of understanding of the Indonesian people about IPR waqf. Habibah et al (2019) used a sample of 324 respondents and showed that most respondents do not know about IPR waqf.…”
Section: Analysis Of the Effect Of Understanding Islamic Religiosity ...supporting
confidence: 90%
See 4 more Smart Citations
“…On the other hand, the result from descriptive respondents regarding the level of understanding is not too high. These results are in accordance with Habibah et al (2019), surveying the level of understanding of the Indonesian people about IPR waqf. Habibah et al (2019) used a sample of 324 respondents and showed that most respondents do not know about IPR waqf.…”
Section: Analysis Of the Effect Of Understanding Islamic Religiosity ...supporting
confidence: 90%
“…Most research conducted from 2012 to 2020 discusses IPR waqf in terms of Islamic law and positive law since IPR as the waqf object is still debatable (Khairunnisa, 2019;Lita, 2020;Niswah, 2018;Saiin et al, 2019;Zaman et al, 2020). Affandi (2017) analyzed IPR waqf in terms of positive law, Islamic law, and the economic impact on society, whilst Habibah et al (2019) studied it regarding the level of people's understanding of IPR waqf. The results of the research by Habibah et al (2019) showed the majority of the total of 324 respondents do not understand the IPR waqf.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations